Air transport performance: current evidences about the efficiency of Italian airports. (1st January 2014) - Brida, Juan Gabriel; Fasone, Vincenzo; Monterubbianesi, Pablo Daniel; Zapata-Aguirre, Sandra
This paper analyses the performance of Italian airports. We construct and estimate a data envelopment analysis, under Charnes, Cooper and Rhodes (CCR), Banker, Charnes and Cooper (BCC) and superfficiency models, in order to obtain efficiency scores for 14 airports for the period 2009–2011. In addition, we use a Malmquist Index for measuring the evolution of the productivity of individual airports along the time. The results show that Genoa, Rome, Naples, Bergamo and Bologna exhibit the best practices when distributing efficiently their production factor available to face an increase in the demand, keeping this behavior during all the period under study. These airports are efficient in both constant return to scale (CRS) and variable return to scale (VRS), indicating that scale is the prevailing source of efficiency.